MENYONTEK (CHEATING) – KECURANGAN AKADEMIK - Yulianto Dirdjosumarto (LPPM POLITEKNIK LP3I BANDUNG, 2016)
Academic dishonesty can be considered as epidemic in all level of education in the world, viruses that spread and attack the academic quality. One of the kinds of academic dishonesty is cheating. The students who become victims of cheating aren’t conscious the influences or impacts of it. War againts cheating should be the first prioriy. Students are potential leader and also worker or employee in the future. Students must be armed with values and ethics or codes of honor or rules of conduct in which unethical behaviors are eliminated. Students should be directed to involve in all process of learning on the basis of integrity. Lecturers, management (institution) and students are expected to take apart in promotion and socialization the importance of integrity in the process of learning and to maintain the quality of academic.